LITHUANIAN PRESS IN CANADA AND REFLECTION OF THE CULTURAL LIFE OF EMIGRANT COMMUNITY IN IT - VĖLAVIČIENĖ, SILVIJA (Knygotyra, 2015)
The new surge of Lithuanian emigrants, who came to Canada after the Second World War (in about 1947) from the camps of displaced persons, did not find in this country neither strong countrymen community nor deep traditions of press in the native language which they used to have in the neighbour country – the United States of America. About 22,000 Lithuanians settled in Canada. As a big number of intellectuals joined former working-class community, new possibilities for development of Lithuanian press arose. Until 2000 over 500 books were printed in Canada, only 50 among them in English. Especially important role in community organizing, native language preservation and national identity rising played Lithuanian weeklies “Nepriklausoma Lietuva” (Independent Lithuania) (Montreal, 1941–2001) and “Tėviškės žiburiai” (Lights of the Mother Country) (launched in Toronto, at the end of 1949 and still being issued). Due to the efforts of the editors – famous historian Adolfas Šapoka (1906–1961) and reverend and philosopher Pranas Gaida-Gaidamavičius(b. 1914) – “Tėviškės žiburiai” became possibly the best weekly of Lithuanian emigrants, popular not only in Canada but in the other countries as Abstractwell. The weekly, finishing its sixth decade, now being edited by Česlovas Stankevičius, managed quietly survive changes of both editors and the exterior of the publication, staying however true to all attitudes of formation of content of publication for all community members. It reflects fullness of the life of Lithuanian community in Canada; therefore the weekly is still popular both among emigrants and in Lithuania itself.Two trends in book publishing especially important for Lithuanian community should be accentuated – Lithuanian education and folk art. A man of merit for Lithuanian education was Antanas Rinkūnas (1909–1985), pedagogue who created the most important textbooks for Lithuanian schools. The brightest advocates of folk art and publishers of books on this topic were famous artists, founders of the Lithuanian Folk Art Institute in Toronto, Anastazija (1906–2005) and Antanas (1906–2005) Tamošaitis. The Lithuanian press in Canada still follows its deep traditions. Lithuanian press and manuscript documents of Lithuanian community activities in Canada are accumulated and preserved in the Lithuanian Museum-Archives, established in 1996, in Toronto.
Keywords: ...